Penerapan Kurikulum Merdeka dalam Pembelajaran Bahasa Indonesia Pada Kelas 4 MI Al-Munawwarah Kota Jambi - Meli Meli; Imran Imran (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The. E.ducation Curriculum Update. continue.s to be. carrie.d out for the. sake. of achie.ving e.ducational goals, the. late.st of which is the. Inde.pe.nde.nt Curriculum. Howe.ve.r, in its imple.me.ntation, proble.ms are. still found so that it is not optimal. This study aims to de.te.rmine. how the. planning, imple.me.ntation, and obstacle.s and e.fforts in imple.me.nting the. inde.pe.nde.nt curriculum. This study use.s a de.scriptive. qualitative. approach with a case. study me.thod. The. subje.cts of the. study we.re. the. Principal, De.puty Curriculum, Indone.sian Language. Te.ache.rs, and Stude.nts. Data colle.ction te.chnique.s use.d obse.rvation, inte.rvie.ws, and docume.nt studie.s. The. re.sults of the. study at MI Al-Munawwarah, Jambi City showe.d that the. imple.me.ntation of the. inde.pe.nde.nt curriculum be.gan with se.ve.ral plans, name.ly by unde.rstanding the. principle.s of the. inde.pe.nde.nt curriculum, compiling te.aching module.s, and making a lite.racy sche.dule.. The. imple.me.ntation of the. inde.pe.nde.nt curriculum has be.e.n going we.ll, e.mphasizing the. importance. of skills and characte.r value.s. Some. of the. obstacle.s found we.re. the. large. numbe.r of te.ache.r administrations, lack of re.ading mate.rials in the. library, and stude.nts having difficulty unde.rstanding the. syllable.s in the. re.ading books. E.fforts to ove.rcome. the.se. obstacle.s are. to provide. fre.e.dom and time. for te.ache.rs to cre.ate. le.arning administration, always work toge.the.r with the. principal, te.ache.rs, and supe.rvisors to me.e.t school ne.e.ds, and utilize. le.arning te.chnology.